A conundrum of West syndrome, behavioural problems and parental expressed emotions: a case report. Issue 5 (7th September 2020) - Malik, Yogender Kumar; Chauhan, Nidhi; Sharma, Akhilesh; Padhy, Susanta
Abstract : West syndrome (WS) is the most common epileptic syndrome in infancy characterised by epileptic spasms, hypsarrhythmia and neurodevelopmental problems. Epileptic spasms remain in many ways a conundrum, and the ideal intervention, as well as how to screen patients to provide optimal care and certainly its genetic cause, remains puzzling. It is important to screen infants for early recognition and intervention to achieve the optimal outcome. We hereby discuss the approach to management of a boy aged 4½ years old with WS and behavioural problems and of parental expressed emotions.